The Effect of Harmonic Components on Dielectric Performance of Solid Insulating Materials - Akin, Firat; Arikan, Oktay (IEEE, 2020)
Solid insulating materials are widely used in electrical installations and devices, commonly for insulation and mechanical support. It is vital to know their performance under different operating conditions. The effect of harmonic components existing in power systems on these materials, is one of the issues to be examined. In this paper, the dielectric performance analyzes of the SBR/NR mixed rubber material at different voltages and frequencies were made experimentally and the obtained results were shared. Experiments were carried out in Yildiz Technical University High Voltage Laboratory using Omicron CPC100/CPTD1.
Keywords: PARTIAL DISCHARGE; Engineering